2015
DOI: 10.1111/ced.12783
|View full text |Cite
|
Sign up to set email alerts
|

mRNA and protein expression of the angiogenesis-related genesEDIL3, AMOTandECM1in mesenchymal stem cells in psoriatic dermis

Abstract: Our data demonstrate for the first time that expression of EDIL3, AMOT and ECM1 is altered in DMSCs in psoriasis, suggesting that EDIL3, AMOT and ECM1 are involved in the excessive angiogenesis and vasodilation observed in psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…An eQTL at the same SNP is reported across many tissues in GTEx, and affects a number of genes in the region, including ECM1, RP11-54A4.2, MRPS21, HORMAD1, GOLPH3L, and TARS2, and in many cases rs6693567 is the lead SNP for those associations. It is not clear which of these genes is most relevant, although ECM1 is reported to have roles in angiogenesis (Han et al 2001) and has been associated with psoriasis (Niu et al 2016) and inflammatory bowel disease (Fisher et al 2008). The most highly expressed of these genes in IPSDSNs is the mitochondrial ribosomal subunit MRPS21 consistent with reports of a link between mitochondrial dysfunction and migraine (Yorns and Hardison 2013).…”
Section: Sensory Neuron Eqtls and Sqtls Overlap With Complex Trait Locimentioning
confidence: 61%
“…An eQTL at the same SNP is reported across many tissues in GTEx, and affects a number of genes in the region, including ECM1, RP11-54A4.2, MRPS21, HORMAD1, GOLPH3L, and TARS2, and in many cases rs6693567 is the lead SNP for those associations. It is not clear which of these genes is most relevant, although ECM1 is reported to have roles in angiogenesis (Han et al 2001) and has been associated with psoriasis (Niu et al 2016) and inflammatory bowel disease (Fisher et al 2008). The most highly expressed of these genes in IPSDSNs is the mitochondrial ribosomal subunit MRPS21 consistent with reports of a link between mitochondrial dysfunction and migraine (Yorns and Hardison 2013).…”
Section: Sensory Neuron Eqtls and Sqtls Overlap With Complex Trait Locimentioning
confidence: 61%
“…In the same year, Niu et al 97 studied the molecular regulation of angiogenesis by DMSCs investigating the mRNA and protein expression of AMOT, EDIL3, and ECM1 in DMSCs isolated from psoriatic skin, with the aim of a better identification of the molecular pathway of angiogenesis in psoriatic skin.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of that study 97 cultured DMSCs, identified by morphology, immunophenotype, and multipotential differentiation, derived from 12 patients with psoriasis and 14 healthy controls. They also evaluated the mRNA and protein expressions of ECM1, EDIL3, and AMOT in the DMSCs using real-time reverse transcription–PCR and Western blotting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations